2016
DOI: 10.1002/jobm.201500475
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of halo‐alkaline and thermostable protease from Halorubrum ezzemoulense strain ETR14 isolated from Sfax solar saltern in Tunisia

Abstract: A total of 54 halophilic strains were isolated from crystallizer TS18 (26 strains) and non-crystallizer M1 (28 strains) ponds and screened for their ability to produce protease, amylase, and lipase activities. Enzymatic assays allowed the selection of thirty-two active strains, among them, the ETR14 strain from TS18 showed maximum protease production yields and therefore, selected for further analysis. The results from 16S rRNA gene sequence analysis revealed that the strain belonged to Halorubrum ezzemoulense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
2
5
0
1
Order By: Relevance
“…Our results showed also that the actinomycete strains constitute potential producers of amylase (69% of the total isolates), followed by protease (52%), cellulase, DNase (39%), and lipase (4%). This is in agreement with our previous studies conducted on the same ponds which found that the most frequent hydrolytic activity among archaeal isolates was observed for amylase and protease [ 21 ]. Assuming that these frequencies are related to the nature of the organic matter in the pond, these results may suggest that carbohydrates and proteins in the sediment are the major carbon sources for the halophilic prokaryotes inhabiting the two ponds [ 19 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed also that the actinomycete strains constitute potential producers of amylase (69% of the total isolates), followed by protease (52%), cellulase, DNase (39%), and lipase (4%). This is in agreement with our previous studies conducted on the same ponds which found that the most frequent hydrolytic activity among archaeal isolates was observed for amylase and protease [ 21 ]. Assuming that these frequencies are related to the nature of the organic matter in the pond, these results may suggest that carbohydrates and proteins in the sediment are the major carbon sources for the halophilic prokaryotes inhabiting the two ponds [ 19 ].…”
Section: Resultssupporting
confidence: 93%
“…Sfax solar saltern, located in the central east of Tunisia, is one of the largest marine salterns in the region. Even though a number of culture-dependent and culture-independent studies were carried out on the biodiversity of eukaryotic [ 19 ] and prokaryotic [ 20 , 21 ] microbial assemblages inhabiting different ponds, there are no reports on any exclusive diversity or biotechnological potential of actinomycetes inhabiting this ecosystem. In a continuous effort to explore the prokaryotic diversity and discover new antimicrobial compounds, we performed a screening procedure to isolate rare halophilic actinomycetes from a concentrator and crystallizer solar saltern ponds and explore their potential to produce drugs against agricultural and human pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were spread on solid Modified Growth Medium [6], containing 5 g peptone and 1 g yeast extract with 12.5 and 23% (w/v) salt concentration at pH 7.5. Prokaryotic isolates were picked after 7-15 days of incubation at 37 °C, based on colony pigmentation, size, and margin and immediately streak-plated at least 3-4 times on fresh agar plates with the appropriate medium until purity was confirmed [7]. Additionally, 41 strains were recovered from previous work.…”
Section: Samples and Strain Isolationmentioning
confidence: 99%
“…Samples were spread on solid Modified Growth Medium [6], containing 5 g peptone, 1 g yeast extract with 12.5 and 23% (w/v) salt concentration, pH 7.5. Prokaryotic isolates were picked after 7-15 days of incubation at 37 °C, based on colony pigmentation, size, and margin and immediately streak-plated at least 3-4 times on fresh agar plates with the appropriate medium until purity was confirmed [7]. Beside this, 41 strains were recovered from previous work.…”
Section: Samples and Strains Isolationmentioning
confidence: 99%